Institutionalized Incivility - Gutkin, Len (Social research, 2025)
, ABSTRACT:, The last decade of academic life has been witness to a peculiar species of moralizing whereby fierce political condemnations ("ritual anathematizations") of disciplines by their practitioners and of scholars by one another are deployed to authorize a comprehensive politicization of knowledge work. As a form of professional maneuvering, these bids for political relevance can be quite effective, but in the long term they degrade the epistemic standards of the fields they afflict, primarily by dogmatically imposing the appearance of expert consensus where none in fact exists. Among other things, disciplinary politicization is a compensatory strategy meant to ward off fears of irrelevance and anxiety about declining prestige.